A novel combined vaccine based on monochimeric VLP co-displaying multiple conserved epitopes against enterovirus 71 and varicella-zoster virus. Issue 20 (9th May 2017) - Wu, Yangtao; Zhu, Rui; Xu, Longfa; Li, Yongchao; Li, Shuxuan; Yu, Hai; Li, Shaowei; Zhu, Hua; Cheng, Tong; Xia, Ningshao
Highlights: Chimeric HBc presenting neutralizing epitopes from EV71 and VZV were constructed. The chimeric VLP elicited protective immunity against EV71 and VZV simultaneously. A novel strategy for design of combined vaccine based on multi-epitopes is proposed. Abstract: Chicken pox and hand, foot and mouth disease (HFMD) are two major infectious diseases that mainly affect infants and children, causing significant morbidity annually. Varicella-zoster virus (VZV) and enterovirus 71 (EV71), respectively, are the principal epidemic pathogens causing these two diseases. To investigate the possibility of developing a novel combined vaccine to prevent chicken pox and HFMD, we constructed three chimeric virus-like particles (VLPs) (termed HBc-V/1/2, HBc-2/V/1 and HBc-1/2/V) based on the hepatitis B core antigen (HBc) carrier that display epitopes derived from VZV-gE, EV71-VP1, and EV71-VP2 in a varied tandem manner. The chimeric HBc can self-assemble into VLPs with these three epitopes displayed on the surface of particles. Epitope-specific antibody characterization suggested that HBc-V/1/2 elicits a balanced antibody response toward these three epitopes, and no immune interference was observed between the three epitopes. Importantly, the anti-HBc-V/1/2 sera could simultaneously neutralize VZV and EV71 and cross-neutralize coxsackievirus A16 (CVA16), another major pathogen causing HFMD. Moreover, the anti-HBc-V/1/2 sera protected neonatal mice from lethal challenge of EV71 and CVA16. Collectively, our study not only demonstrated that HBc-V/1/2 is a promising candidate combined vaccine for HFMD and Chicken pox but also provides a novel strategy for the design of combined vaccines.